Canakinumab in systemic juvenile idiopathic arthritis: real-world data from a retrospective Italian cohort. (3rd August 2021) - De Matteis, Arianna; Bracaglia, Claudia; Pires Marafon, Denise; Piscitelli, Anna Lucia; Alessio, Maria; Naddei, Roberta; Orlando, Francesca; Filocamo, Giovanni; Minoia, Francesca; Ravelli, Angelo; Tibaldi, Jessica; Cimaz, Rolando; et al.
Abstract: Objective: The objective of this study was to use real-world data to evaluate the effectiveness and safety of canakinumab in Italian patients with systemic JIA (sJIA). Methods: A retrospective multicentre study of children with sJIA was performed. Clinical features, laboratory parameters and adverse events were collected at baseline, and 6 and 12 months after starting canakinumab. The primary outcome measure of effectiveness was clinically inactive disease (CID) off glucocorticoids (GCs) treatment at 6 months. Results: A total of 80 children from 15 Italian centres were analysed. Of the 12 patients who started canakinumab in CID while receiving anakinra, all maintained CID. Of the 68 with active disease at baseline, 57.4% achieved CID off GCs at 6 months and 63.8% at 12 months. In univariate analysis, the variables significantly related to non-response were number of active joints (NAJs) ≥5, history of macrophage activation syndrome (MAS) and disease duration. Multivariate analysis confirmed the association between non-response and NAJs ≥5 [odds ratio (OR) 6.37 (95% CI: 1.69, 24.02), P = 0.006] and between non-response and history of MAS [OR 3.53 (95% CI: 1.06, 11.70), P = 0.039]. No serious adverse events were recorded in this series. There were two cases of MAS during canakinumab, leading to a rate of 2.9 episodes per 100 patient years. Conclusion: We have confirmed, using real-world data, the efficacy of canakinumab in sJIA in a multicentric cohort. History of MAS and higher NAJ were associated with lower probability of achieving CID.